Bonjour Sousou79 ! :)
On va partir du fait que :
[tex] (a - b)^2 \geq 0[/tex]
[tex]a^2 - 2ab + b^2 \geq 0[/tex]
[tex]a^2 + b^2 \geq 2ab[/tex]
[tex] \frac{a^2+b^2}{ab} \geq 2 [/tex]
[tex] \frac{a^2}{ab} + \frac{b^2}{ab} \geq 2[/tex]
[tex] \frac{a}{b} + \frac{b}{a} \geq 2[/tex]
Voilà pour le premier ! :)
Passons au deuxième :
[tex](a + b)( \frac{1}{a} + \frac{1}{b}) = 1 + \frac{a}{b} + \frac{b}{a} + 1 = 2 + \frac{a}{b} + \frac{b}{a} [/tex]
Or : [tex]\frac{a}{b} + \frac{b}{a} \geq 2[/tex]
Donc : [tex](a + b)( \frac{1}{a} + \frac{1}{b}) = 2 + \frac{a}{b} + \frac{b}{a} \geq 2 + 2[/tex]
Conclusion : [tex](a + b)( \frac{1}{a} + \frac{1}{b}) \geq 4[/tex]
Voilà, j'espère t'avoir aidé. :)